Effectiveness of Acupressure and Eucalyptus Oil for Toddler Respiratory Infections in Indonesia: Efektivitas Akupresur dan Minyak Kayu Putih untuk Infeksi Saluran Pernapasan Balita di Indonesia - Aini, Latifatul; Rinata, Evi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effectiveness of acupressure and simple eucalyptus oil inhalation in reducing cold and cough severity among toddlers under five years old in Indonesia, where respiratory infections account for a significant portion of childhood mortality. Conducted using a quasi-experimental design with a pretest-posttest approach, the research involved 33 toddlers from Jenisgelaran Village, Bareng, Jombang, randomly assigned to control, acupressure-only, and combined treatment groups. Data collected through observation sheets and the Integrated Management of Childhood Illness (IMCI) classification showed significant improvements in symptom severity in the combined treatment group (P = 0.01), while One Way ANOVA results indicated no overall significant effect (P = 0.06) across groups. These findings suggest potential benefits of combined therapy but highlight the need for standardized eucalyptus oil types and clearer treatment protocols to enhance therapeutic outcomes in future studies aiming to alleviate respiratory symptoms in young children. Highlights: Quasi-experimental design with pretest-posttest approach. Significant improvement in symptom severity in combined treatment group. Need for standardized eucalyptus oil types and clear treatment protocols for optimal therapeutic outcomes. Keywords: Acupressure, Eucalyptus Oil Inhalation, Toddlers, Respiratory Infections, Indonesia